Opioid-sparing effects of medical cannabis or cannabinoids for chronic pain: a systematic review and meta-analysis of randomised and observational studies. Issue 7 (28th July 2021) - Noori, Atefeh; Miroshnychenko, Anna; Shergill, Yaadwinder; Ashoorion, Vahid; Rehman, Yasir; Couban, Rachel J; Buckley, D Norman; Thabane, Lehana; Bhandari, Mohit; Guyatt, Gordon H; Agoritsas, Thomas; Busse, Jason W
Abstract : Objective: To assess the efficacy and harms of adding medical cannabis to prescription opioids among people living with chronic pain. Design: Systematic review. Data sources: CENTRAL, EMBASE and MEDLINE. Main outcomes and measures: Opioid dose reduction, pain relief, sleep disturbance, physical and emotional functioning and adverse events. Study selection criteria and methods: We included studies that enrolled patients with chronic pain receiving prescription opioids and explored the impact of adding medical cannabis. We used Grading of Recommendations Assessment, Development and Evaluation to assess the certainty of evidence for each outcome. Results: Eligible studies included five randomised trials (all enrolling chronic cancer-pain patients) and 12 observational studies. All randomised trials instructed participants to maintain their opioid dose, which resulted in a very low certainty evidence that adding cannabis has little or no impact on opioid use (weighted mean difference (WMD) −3.4 milligram morphine equivalent (MME); 95% CI (CI) −12.7 to 5.8). Randomised trials provided high certainty evidence that cannabis addition had little or no effect on pain relief (WMD −0.18 cm; 95% CI −0.38 to 0.02; on a 10 cm Visual Analogue Scale (VAS) for pain) or sleep disturbance (WMD −0.22 cm; 95% CI −0.4 to −0.06; on a 10 cm VAS for sleep disturbance; minimally important difference is 1 cm) among chronic cancer pain patients. Addition of cannabis likely increases nausea (relative risk (RR) 1.43; 95% CI 1.04 to 1.96; risk difference (RD) 4%, 95% CI 0% to 7%) and vomiting (RR 1.5; 95% CI 1.01 to 2.24; RD 3%; 95% CI 0% to 6%) (both moderate certainty) and may have no effect on constipation (RR 0.85; 95% CI 0.54 to 1.35; RD −1%; 95% CI −4% to 2%) (low certainty). Eight observational studies provided very low certainty evidence that adding cannabis reduced opioid use (WMD −22.5 MME; 95% CI −43.06 to −1.97). Conclusion: Opioid-sparing effects of medical cannabis for chronic pain remain uncertain due to very low certainty evidence. PROSPERO registration number CRD42018091098.